In-silico comparison of drugs and natural compounds towards inflammation disease / Azzatul Amira Azman - Azman, Azzatul Amira; Mohd Mokhlis, Nur Hannah; Musthafa, Ahmad Adib Asyraf; Ariza Fattah, Muhammad Zahin Ikhwan
The study on the inhibition of Interleukin-1, Cyclooxygenase-2, Toll-like receptor 4, and Human Phospholipase A2 was an important approach for inflammation treatment. The inhibition of the protein target of inflammation, Interleukin-1, Cyclooxygenase-2, Toll-like receptor 4, and Human Phospholipase A2 using synthetic and natural inhibitors were studied. Synthetic compounds Ibuprofen, Flurbiprofen, and Indomethacin and natural compounds such as Curcumin, Gallic acid, Artemisinin, Rosmarinic acid, and Andrographolide was used in this study. The purpose of this research is to identify the potential inhibitor of natural compound as anti-inflammation towards Interleukin-1, Cyclooxygenase-2, Toll-like receptor 4, and Human Phospholipase A2. In this research, molecular docking methods were used to identify the compound that has the best interaction energy towards the Interleukin-1, Cyclooxygenase-2, Toll-like receptor 4, and Human Phospholipase A2 protein targets. In structure-based drug design, molecular docking method is used because of their ability to predict the binding-conformation of small-molecule ligands to the target binding site as the main objective of molecular docking is to attain a ligand-receptor complex with optimized conformation and with the intention of processing less binding free energy. The results obtained from the docking using Autodock Vina software showed that the best affinity binding was observed. The molecular interactions were then further analyzed using Discovery Studio Visualizer. Based on the molecular docking studies, Andrographolide, Artemisinin, Rosmarinic Acid and Curcumin was chosen as the potential inhibitor chosen for 5UCA, 2NRU, 3PGH for anti-inflammatory. It is hoped that this study can create new discoveries in an effort to find potential inhibitors for inflammatory disease.